2005
DOI: 10.1007/s10567-005-2341-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Relationships and Sex Differences in the Development of Conduct Problems

Abstract: This article investigates the role of interpersonal relationships in shaping sex differences in the manifestation, etiology, and developmental course of conduct problems and their treatment needs. The review examines whether: (1) Girls' conduct problems are more likely than boys' to manifest as a function of disrupted relationships with caretakers and peers; (2) For girls more than for boys, the outcomes of conduct problems in adolescence and adulthood, and related treatment needs, are more likely to be a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 147 publications
(160 reference statements)
3
44
0
Order By: Relevance
“…Finally, lower self-regulation in the preschool period would be longitudinally predictive of higher externalizing behavior problems at kindergarten age, after controlling for prior levels of externalizing behavior problems. The model also includes child gender as a covariate, because boys have lower self-regulation (Kochanska, Murray, & Harlan, 2000) and higher externalizing behavior problems compared with girls (for a review, see Ehrensaft, 2005). …”
Section: Conceptual Modelmentioning
confidence: 99%
“…Finally, lower self-regulation in the preschool period would be longitudinally predictive of higher externalizing behavior problems at kindergarten age, after controlling for prior levels of externalizing behavior problems. The model also includes child gender as a covariate, because boys have lower self-regulation (Kochanska, Murray, & Harlan, 2000) and higher externalizing behavior problems compared with girls (for a review, see Ehrensaft, 2005). …”
Section: Conceptual Modelmentioning
confidence: 99%
“…In a review of gender differences in the development of conduct problems, Ehrensaft (2005) concluded that girls were more likely than boys to develop conduct problems because of problems in close family and peer relationships. On the other hand, Moffitt and colleagues (2001) found that similar risk factors predicted girls' and boys' antisocial behaviour.…”
Section: Early Adolescent Relationship Problems and Delinquency Trajementioning
confidence: 99%
“…Given the prevalence of abuse and impoverished coping skills of girls with early aggressive histories (Ehrensaft 2005;Walsh et al 2002;Yuile 2007), programs designed for these girls need to consider fostering prosocial and relationship-based learning, and encouraging the development of a positive gender identity and sense of agency (Hipwell and Loeber 2006). As well, Kazdin and Crowley (1997) hypothesized that cognitively based treatments may effect a better treatment response for girls, as females often exhibit greater skills in perspective-taking, and empathy.…”
Section: Why Intervene With Aggressive Young Girls?mentioning
confidence: 99%
“…The few referred girls were admitted to the SNAP® (StopNow-And-Plan) Under 12 Outreach Project (ORP), an evidence-based intervention designed primarily for boys (Augimeri et al 2007). Growing evidence of aggressive girls' negative life course (Ehrensaft 2005;Kann and Hanna 2000) provided the impetus for clinicians and researchers to develop an empirically driven, gender-sensitive program for young aggressive girls and their families. In this paper, we describe an evaluation of the SNAP® Girls Connection (GC), introduced in 1996.…”
mentioning
confidence: 99%